Nghiên cứu chế tạo Ferit ba pha la - Châu, Nguyễn; Mạnh, Đỗ Hùng; Tuấn, Phạm Anh; Phúc, Nguyễn Xuân; Tường, Lê Thị Cát; Huân, Lê Văn; Cường, Trần Đình; Thanh, Phùng Quốc; Quyên, Nguyễn Hồng (VNU Journal of Science: Natural Sciences and Technology; Vol 6 No 3, 1990)
Abstract